Home support variables affecting the well-being of children with cerebral palsv in selected children’s homes in Oyo state, Nigeria (2022)
The study investigated how some home support variables (home companionship support. home financial support and home physical exercise) affect the vvell-being of children with cerebral palsy in selected children's homes in Oyo State. Nigeria. The descriptive survey research designs of correlational and ex-post-facto types were employed for the study. The purposive sampling technique was used to select 153 participants for the study. They comprised 61 male and 92 female children with cerebral palsy whose ages range from 5 to 20 years and above. Four hypotheses were tested in the study at a 0.05 level of significance, using Multiple regression and Pearson Product Moment Correlation. There was a significant relationship between each of the home support variables and well-being of children with cerebral palsy in selected children's homes in Oyo State as follow: home companionship support and well-being (r = .575, N 153, p< .05), home financial support and well- being (r = .672, N = 153, p< .05) and home physical exercise and well-being (r= .359, N = 153, p< .05). There was a joint significant effect of home support variables (home companionship support, home financial support and home physical exercise) on the well-being of children with cerebral palsy in selected children's homes in Oyo State (R = .673, R: = .452, Adjusted R2 = .441. Standard error of estimate = 6.870. F(3/l 49) = 41.021, P<.05). The study also revealed significant relative effects of each of the home support variables on well-being of children with cerebral palsy in selected children's homes in Oyo State as follow: home financial support (P= 0.432. t = 9.825. p<.05), home companionship support (P = 0.140. t = 5.439. p<.05. and home physical exercise (P = 0.168, t = 4.352, p<.05). Based on the above findings some useful recommendations were made in the study which would go a long way in helping parents, homes, schools and other caregivers meet the needs of children with cerebral palsy and other children alike.